Innovation, social responsibility and sustainability - Crowther, David; Seifi, Shahla (Emerald Publishing Limited, 2023)
While global challenges such as a future pandemics and global warming seem insurmountable, innovation and cumulative small changes can help towards managing such disruptive events. Innovation can encompass a new way of doing things, new products and services, and new solutions; in organizations where innovation can flourish, progress and resilience can be achieved. This edited collection draws together a number of chapters, organized into two parts - developing social responsibility and developing sustainability - both of which are interlinked and interdependent. Topics presented range from: mandatory CSR in the banking industry to the professional integration of displaced persons to knowledge for and about sustainability, and many more. The diversity of the chapters gift readers an interdisciplinary examination of innovation, social responsibility and sustainability. Developments in Corporate Governance and Responsibility offers the latest research on topical issues by international experts and has practical relevance to business managers.
Includes index.
Keywords: Social responsibility of business.; Technological innovations.; Business & Economics -- Economics / Social & Behavioral.; Business ethics & social responsibility.; elektronické knihy; electronic books